Odontogenic choristoma presenting as dermolipoma. (2nd November 2019) - Men, Clara J.; Wu, Frances; Lee, Bradford W.; Lin, Jonathan H.; Korn, Bobby S.; Kikkawa, Don O.
ABSTRACT: A 5-year-old otherwise healthy girl presented to the oculoplastic service with a painless superotemporal subconjunctival mass in the left eye. Visual acuity was within normal limits, and there was no evidence of proptosis or orbital enlargement. Excision was performed to remove the anterior portion of the mass for alleviation of symptoms. On histopathological analysis, the mass was comprised of fibroadipose tissue consistent with dermolipoma and contained a hard nodule found to be a calcified tooth. In the periocular region, odontogenic choristoma (tooth) is a rare lesion, and has been reported to occur within teratomas, dermoid cysts, and displaced oral embryonic epithelium. We describe an unusual case of a tooth occurring within a sporadic dermolipoma. The clinical presentation, examination, management, and histopathology are reviewed.